Libyan PM threatens to take deterrent measures against Awqaf Authority - Assad, Abdulkader (The Libya Observer, 2024)
The Prime Minister of the Government of National Unity Abdul Hamid Dbeibah sent a letter to the Head of the Endowments and Islamic Affairs Authority (Awqaf Authority) in his government, Mohammed Al-Abani, regarding Muslim Ibadis.
Keywords: Vie politique – Djebel Nefousa; Waqf (fondations) – Djebel Nefousa